PENERAPAN METODE ANALYTICAL HIERARCHY PROCESS DALAM PENENTUAN PRIORITAS PENANGANAN PEMELIHARAAN JALAN DI KOTA BANDA ACEH - M. Saleh, Sofyan; Abbas Majid, Ibnu; Firdasari, Firdasari (Jurnal Transportasi, 2013)
Determination of road maintenance involves complex multi-criteria in decision making process. Analytical Hierarchy Process (AHP) method has been used to determine the weight of criteria in evaluating the road maintenance priority. In this study, the priority decisions for maintaining collector roads in Banda Aceh city were determined using the AHP method. The objective of this study is to describe the decision making process in determining the road maintenance handling priority accurately involving the key persons. There are 4 (four) criteria used, namely road condition, traffic volume, policy, and land use factors. The results showed that the highest criteria weight was achieved by road condition with a score of 0,454, followed by traffic volume (0.255) and land use (0.158), respectively. Surprisingly, the lowest score was obtained by policy factor. It was really beyond expectation since road maintenance priorities were usually relied on the government policy. The results indicated that road condition and traffic volume were the main factors in determining the road maintenance priorities.Keywords: road handling priority, road condition, traffic volume, AHP method